Mujeres de Palacio: la jugada con referencias lingüísticas y culturales de la mujer. Caso de actividad publicitaria de grandes almacenes mexicanos - Kwiatkowska-Faryś, Edyta; Faryś, Michał (Investigationes Linguisticae, 2007)
For almost a decade Mexican department stores Palacio de Hierro have been running a media campaign called Soy Totalmente Palacio (I am totally the Palace). It is an image campaign, a novelty in the Spanish-speaking world, underpinned on playing with the linguistic and cultural stereotypes of a woman. The ads gained a broad social resonance and were followed up with a public debate on the image of a woman. The article presents types and ways of using the applied linguistic schemes and analyzes the mechanisms of the successful brand image building thanks to the use of stereotypes.